2021
DOI: 10.1111/den.14058
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of endoscopic resection for colorectal laterally spreading tumors: Endoscopic submucosal dissection versus piecemeal endoscopic mucosal resection

Abstract: Objectives:The cost-effectiveness of endoscopic submucosal dissection (ESD) and piecemeal endoscopic mucosal resection (pEMR) for colorectal laterally spreading tumors (LSTs) remains unclear. We examined the cost-effectiveness of these procedures for cases of colon/rectal LST-non-granular-type ≥2 cm and LST-granular-mixed-type ≥3 cm. Methods:We performed a simulation model analysis using parameters based on clinical data from the National Cancer Center Hospital, Tokyo, and previous literature. The number of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…LSTs of less than 20 mm in diameter can be treated with EMR, 24 while ESD is recommended for those with a diameter exceeding 20 mm or larger as it has a higher overall resection rate and lower local recurrence rate. 25,26 Our study found that there was no significant difference in the pathological features of JNET2B-low and JNET2B-high LSTs when using a cut-off value of 20 mm for lesion size. Therefore, the classification of LSTs into JNET2B-low and JNET2B-high is also suitable for tumors of different sizes.…”
Section: Patients N (%)mentioning
confidence: 57%
“…LSTs of less than 20 mm in diameter can be treated with EMR, 24 while ESD is recommended for those with a diameter exceeding 20 mm or larger as it has a higher overall resection rate and lower local recurrence rate. 25,26 Our study found that there was no significant difference in the pathological features of JNET2B-low and JNET2B-high LSTs when using a cut-off value of 20 mm for lesion size. Therefore, the classification of LSTs into JNET2B-low and JNET2B-high is also suitable for tumors of different sizes.…”
Section: Patients N (%)mentioning
confidence: 57%
“…The treatment procedure was determined by each lesion characteristic as follows: First, all adenomas: endoscopic resection including hot snare polypectomy, cold snare polypectomy, and endoscopic mucosal resection, Stage 0 cancer <20 mm: hot snare polypectomy or endoscopic mucosal resection, Stage 0 cancer ≥20 mm: endoscopic submucosal dissection (ESD), Stage 1 cancer <1000 μm of submucosa: ESD, Stage 1 cancer >1000 μm or Stage 2 cancer: surgery, Stage 3 cancer: surgery ± chemotherapy, Stage 4 cancer: chemotherapy. The initial cost for the treatment of stage 0–4 cancer was defined in previous reports that investigated the treatment cost for CRC under the Japanese healthcare insurance system 12,13 …”
Section: Methodsmentioning
confidence: 99%
“…The initial cost for the treatment of stage 0-4 cancer was defined in previous reports that investigated the treatment cost for CRC under the Japanese healthcare insurance system. 12,13 Second, the number of patient examinations needed for the analysis was based on a previous report. 14 In this analysis, the number of examinations required to treat one adenoma, advanced adenoma, or cancer was calculated for the two strategies.…”
Section: Cost-effectiveness Simulationmentioning
confidence: 99%